Barriers and drivers of teachers’ digital competencies: A systematic literature review (Educational Knowledge, 2025)
The development of digital competencies among teachers is a pressing challenge in today’s rapidly evolving educational landscape. This study aims to synthesize the current state of research on the factors influencing digital competency acquisition among Latin American teachers. Using a systematic review methodology, empirical studies published between 2018 and 2023 were analyzed. The findings highlight critical facilitators such as access to resources, pedagogical training, and institutional support. However, significant barriers persist, including limited time for practice, inadequate pedagogical models, and the lack of recognition for the efforts involved. By clarifying these factors, this study provides valuable insights for policymakers, teacher trainers, and researchers aiming to effectively foster digital competencies.
Keywords: Digital competencies; teacher training; systematic review; enablers; barriers; Latin America